Die geographischen Auswirkungen des Erdbebens vom 22. Mai 1960 im Kleinen Süden Chiles: Vorläufiger Bericht - Weischet, Wolfgang (ERDKUNDE, 1960)
The geographical effects of the earth-quakes of 21rst and 22nd May 1960 might be divided into 1. direct effects of the earth-quakes, 2. land depression, 3. seismic waves in the coastal region, 4. land slides and 5. volcanic eruptions. The centre of the earth-quake activity was on the mainland west of the northern part of Lake Llanquihue. The tectonic and geomorphological conditions in the Basin of Valdivia had the effect that here a secondary centre of great seismic acceleration originated. Recent natural and artificial deposits reinforced here and there the effects of the earth-quakes between Middle-Chile and the southern part of the province of Cautin. The observations hitherto made show depressions of about 1,40—1,50 metres, which are quite independent of the geological structure along the coast-line. The seismic waves occured immediately after the earthquake. At first only an extraordinary rise and fall of the tide was noticed. This was followed by tidal waves with pronounced breakers of up to 10 metres height, which damaged heavily the land around the river mouths and along the coasts. About 2000 people are said to have been killed by these seismic waves alone. The waves running back often excavated the sand-barriers in the river mouths. As far as it is known spontaneous land slides were concentrated in three zones: the coastal cliffs, the cliffs of Lake Llanquihue, and the western slopes of the Andine High Cordilleras. In the coastal region the weathered ground slided down. The banks of Lake Llanquihue (glacial material, 70 metres high, sloping 50 degrees and more) were only superficially deformed. The base of the steep slopes remained uneffected. Larger mass-movements occured in the marginal zones of the High Cordilleras, especially where tectonic structure-lines are found (see fig. 1). Thus dikes were deposited across the valleys damming up the water of the rivers. Settlements were overflooded. When the dams near Valdivia were blown up, the flowing waters reached up to 7 metres. In the whole valley heavy damages were brought about by erosion and deposition. Of the volcanoes only the Puyehue became active. On its western slope, in a height of about 2000 metres, seven new craters came into existence. The volcanic ashes were spread mainly eastwards.